2022
DOI: 10.1108/ara-06-2021-0107
|View full text |Cite
|
Sign up to set email alerts
|

CSR committees, politicians and CSR efforts

Abstract: PurposeThe purpose of this paper is to study the relationships among the presence of corporate social responsibility (CSR) committee, politicians on CSR committee and CSR disclosure in 10-Ks using data from S&P 500 firms during 2005–2013.Design/methodology/approachThe authors manually check the information of CSR committees as well as committees with CSR/sustainability functions from proxy statements (DEF 14a). CSR disclosure from 10-Ks is obtained by using a Python library named Beautiful Soup 4 to clean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…(2021)). Sustainability committees have played a significant role in sustainability disclosure and performance (Guo and Yu, 2022). We add all control variables at the firm level (governance, leverage, size) and country level (GDP growth, country governance, multiple listings and common law) to the first step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021)). Sustainability committees have played a significant role in sustainability disclosure and performance (Guo and Yu, 2022). We add all control variables at the firm level (governance, leverage, size) and country level (GDP growth, country governance, multiple listings and common law) to the first step.…”
Section: Resultsmentioning
confidence: 99%
“…Following the best practice of conducting Heckman tests (Certo et al, 2016), our exclusion restriction in the first step probit model is whether a firm has a sustainability committee (see ). Sustainability committees have played a significant role in sustainability disclosure and performance (Guo and Yu, 2022). We add all control variables at the firm level (governance, leverage, size) and country level (GDP growth, country governance, multiple listings and common law) to the first step.…”
Section: Robustness Checks: Self-reportingmentioning
confidence: 99%
“…However, the study was conducted in the USA, a developed country, leading to a contextual gap in Tanzania's public corporations. Equally, [33] studied CSR Committees, politicians, and CSR efforts in China. The study found that the inclusion of politicians on CSR committees is connected with CSR disclosure and CSR performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Responsible investing (RI) is getting traction in investment by stakeholders worldwide (Friede et al, 2015). The concerns of the sustainability of the environment, impact on social causes and good governance of the firms practically force firms to subsume RI in investment decision-making in the broader aspect (Guo and Yu, 2022). It can be construed that the investment community finds RI to have financial value (Amel-Zadeh and Serafeim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This change of perception makes socially responsible investment or RI a priority for fund managers and asset owners. The inclination of firms for environment, social and governance (ESG) may not be seen as a competitive advantage but as a risk to be incorporated in investment decision-making ARA 32,1 70 (Amel-Zadeh and Serafeim, 2018;Guo and Yu, 2022). A report by Principles for Responsible Investing claims that assets under management worth more than US$120tn are by the signatory of the cause of RI (Pri, 2021;Friede et al, 2015;Eccles et al, 2017).…”
Section: Introductionmentioning
confidence: 99%